Percepción de riesgo de Síndrome Urémico Hemolítico - Broglio, A. (2021)
Among the foodborne zoonoses, Shiga toxin-producing Escherichia coli stands out due to its impact on health. This microorganism, whose main reservoirs are ruminants, reaches the susceptible host through the contamination of meat, its processing, transport, trade and consumption. It generally affects children younger than 5 years, causing variable clinical manifestations ranging from diarrhea to Hemolytic Uremic Syndrome (HUS), in which many cases required kidney transplantation. This disease is endemic in Argentina. As part of the studies of exposure to risk factors in this disease, we have studied the perception of risk of people in various contexts. To do this, we developed and validated a survey model of knowledge, attitudes and practices aimed at adults. This survey was applied in the Autonomous City of Buenos Aires, Tierra del Fuego and Exaltación de la Cruz. Studies show the influence of cultural-belief factors on the perception of subjective risk (individual) and the weakness of isolated communicative actions compared to the perception of real and collective risk. The influence of intervention models based on health promotion campaigns or programs is discussed.